2020
DOI: 10.1093/pubmed/fdaa092
|View full text |Cite
|
Sign up to set email alerts
|

Establishing prison-led contact tracing to prevent outbreaks of COVID-19 in prisons in Ireland

Abstract: Background Preventing transmission of COVID-19 within prisons is both important and challenging. The confined conditions in prisons can encourage person-to-person spread with the potential for outbreaks occurring. Contact tracing is an important contributor to the longer-term management strategy for COVID-19 in prisons as well as in the community but is highly resource-intensive. This paper describes the approach to contact tracing taken by the Irish Prison Service (IPS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 1 publication
0
39
0
6
Order By: Relevance
“…(3) Technical improvement of the health management of the corrections facilities must be continuously supported to prevent the possible new wave of virus infection. For example, Clarke et al (2020) reported the government initiative in Ireland to establish an approach of contact tracing in prisons in which all prisons, and two support agencies, have fully operative internal teams that conduct contact tracing and manage quarantine procedures among the PDLs. On the other hand, as more PDLs are released in the Philippines, there is also a demand to improve the community corrections that will supervise them once they are outside.…”
Section: Resultsmentioning
confidence: 99%
“…(3) Technical improvement of the health management of the corrections facilities must be continuously supported to prevent the possible new wave of virus infection. For example, Clarke et al (2020) reported the government initiative in Ireland to establish an approach of contact tracing in prisons in which all prisons, and two support agencies, have fully operative internal teams that conduct contact tracing and manage quarantine procedures among the PDLs. On the other hand, as more PDLs are released in the Philippines, there is also a demand to improve the community corrections that will supervise them once they are outside.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, video technology is used to monitor the activities of inmates or residents in correctional or detention settings. Our outbreak management protocol is similar to the one developed by the Irish Prison System and described by Clark et al 7 The advantages of video review include the following: (1) Immediate identification of close contacts allowing recommendations for immediate testing, medical isolation, and quarantine; (2) Three hundred sixty degree video angles of the route and location of the individual for up to 30 days prior to identification; (3) Identification of the details of each exposure incident, including observation of whether employees adhered to the recommended infection control practices, and quantification of the duration of exposure using the video timestamp; (4) supplementation of the oral interview in cases where the narrative regarding activities or contacts was unclear. Video review helped improve compliance with infection control protocols because it revealed unidentified issues and areas in need of improvement, such as, appropriate masking and enforcement of social distancing.…”
Section: Communicationsmentioning
confidence: 99%
“…It also allowed the OMT to implement changes such as requiring floor nurses to wear face shields, and installation of sneeze guards on nursing carts. Authors in an earlier study describe limitations such as the lengthy time required to review the video footage, and the accuracy of individual identification if the video was outside the facility or in one of the camera blind spots 7 , 8 . For residents, none of the secondary cases led to further infections thus justifying the cost benefit of the labor intensive video footage reviews to identify unprotected exposures to confirmed cases .…”
Section: Communicationsmentioning
confidence: 99%
“…Examples of BC Corrections' health-informed approach include screening and testing everyone who enters custody, operating induction units for asymptomatic individuals and isolation for suspected and confirmed individuals, and providing staff with PPE when physical distance cannot be maintained. BC Corrections also has a procedure that allows for contact tracing, which Clarke et al (2020) argue is a key component of controlling transmission of COVID-19 in correctional institutions. Another primary component of responding to the pandemic through a health-informed approach is ensuring that correctional authorities do not simply default to solitary confinement as the primary solution to minimize transmission of the virus.…”
Section: Lessons Learned: Recommendations For Other Jurisdictions To mentioning
confidence: 99%